Analisis Pengaruh Gender, Beban Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan - Arvin Yunita Nurul Wilda; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study aims to describe gender, workload, work motivation and employee performance of PT. Bringin Gigantara KC Surabaya, knowing the effect of gender, workload, work motivation on employee performance. This research was conducted at PT. Bringin Gigantara KC Surabaya with a sample size of 50 respondents.The data analysis technique uses multiple linear regression analysis. Descriptive analysis results show that the employees of PT. Bringin Gigantara perceives agreeing on all research variables namely gender, workload, work motivation and employee performance. Gender has a significant effect on the performance of employees of PT. Bringin Gigantara. Workload has a significant effect on the performance of employees of PT. Bringin Gigantara. Work motivation has a significant effect on the performance of employees of PT. Bringin Gigantara. gender, workload, and work motivation simultaneously have a significant effect on the performance of the employees of PT. Bringin Gigantara KC Surabaya.Keywords: gender, workload, work motivation and employee performance.